A review of amnestic MCI screening in east/southeast Asian older adults with low education: implications for early informant‐clinician collaboration. (10th November 2014) - Lim, Magdalene L.; Gomez, Rowena; Koopman, Cheryl
<x xml:space="preserve">Abstract</x> Objective The aim of this study is to review the recent literature on established cognitive tests and appropriate screening methods for amnestic mild cognitive impairment (MCI) in East/Southeast Asian older adults with a focus on those with low education. Design Peer‐reviewed empirical studies conducted in Asia (China, Hong Kong, Japan, Korea, Singapore, and Taiwan) were identified using databases in psychology and medicine with combinations of the search terms "mild cognitive impairment, " "dementia, " "screening, " "literacy, " "illiteracy, " "low education, " "informant, " "family, " "cognitive test, " "memory complaints, " "activities of daily living, " and "clinical dementia rating, " limiting articles to those published in English since 1 January 2002. Of note, is that the term "amnestic mild cognitive impairment" was not used for searching the articles because the related cognitive impairment were often categorized non‐specifically as MCI, but participants included those with amnestic cognitive challenges. Hence, the general term "MCI" has been used often throughout the text. Results Twelve studies that examined MCI screens were identified. An integrative approach using a combination of cognitive test and informant‐based measure may be more sensitive or accurate than using any single screening method alone. Conclusion MCI misdiagnosis may be prevalent, highlighting the need for early collaborative work between informants and clinicians to improve the accuracy of this diagnosis in older Asian adults with low education. Findings were suggestive, although restricted in generalizability even within similar cultural groups or neighboring regions. Clinical application is limited, but some findings provide guidance for future research. Copyright © 2014 John Wiley & Sons, Ltd.